Balancing epistemic quality and equal participation in a system approach to deliberative democracy. (4th May 2017) - Chambers, Simone
Abstract: In this paper, I argue that the asymmetrical mediated communication of the broad democratic public sphere can profitably be understood through the lens of deliberative democracy only if we adopt a system approach to deliberation. A system approach, however, often introduces a division of labor between ordinary citizens and experts (knowledgeable elites). Although this division of labor is unavoidable and I believe compatible with a deliberative principle of legitimacy, it flirts with elitist theories of democracy: epistemic elites come up with the agendas, ideas, and policy positions and democratic publics ratify or repudiate the agendas but do not generate or really engage with them. This I argue would violate an essential defining feature of deliberative democracy, namely that epistemic quality and equal participation are tightly linked. I turn to Habermas and his idea of a feedback loop as a possible solution to this dilemma.